The utilization of instagram social-media in the marketing strategy of the marketing department of Yogyakarta city tourism office - Bernardinus Unggul Rinando; Angga Intueri Mahendra Purbakusuma (Institute of Computer Science (IOCS), 2023)
This research was conducted to find out and analyze the use of Instagram social media in the marketing strategy of the Marketing Department of Yogyakarta City Tourism Office. The type of research used in this research is descriptive qualitative research. The object of this study was from the Instagram account @wisata.jogjakota which the Marketing Department of the Yogyakarta City Tourism Office manages. The analysis technique used in this study is the Miles and Huberman analysis model which consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, and concluding/verification. Instagram social media in the marketing strategy of the Tourism Marketing Department of Yogyakarta City show that technological developments in this era affect how people search for and share information. Instagram social media in the marketing strategy of the Tourism Marketing Department of Yogyakarta City show that technological developments in this era affect how people search for and share information.